PENGARUH RESILIENSI TERHADAP INTERAKSI SOSIAL REMAJA MASJID DI KELURAHAN MINAS JAYA KECAMATAN MINAS KABUPATEN SIAK - Romi Oktavianus; Daeng Ayub Natuna; Said Suhil Achmad (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: This study aims to determine how high the social interaction and resilience of youth mosques in Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak, find out how high the social interaction of young mosques in Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak, know how high the youth resilience of mosques in the Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak, and knowing the positive and significant influence between resilience on the social interaction of teenage mosques in the Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak. This type of quantitative research using the ex post facto method tests two variables to be studied to determine how much influence the independent and dependent variables have. The population in this study were the teenage mosques in Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak as many as 82 teenagers in the mosque. The sample in this study amounted to 46 adolescent mosques in Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak. The instrument used was a questionnaire. Based on the analysis of the respondents' demographic factors, the social interaction of mosque youths obtained high results with a mean of 3,77 and resilience of mosque youth obtained high results with a mean of 3,78. Based on the descriptive analysis of the social interaction variable of 3.80 and resilience of 3.84 with a high interpretation. Obtained a significant and positive effect of resilience variable (X) on Social Interaction (Y) of the Youth of Kelurahan Minas Jaya Kecamatan Minas Kabupaten Siak, the big influence is 63.10% with a high interpretation, because there is still 36.90% determined by other factors. who were not part of this study.Key Word: Social Interaction, Resilience, Mosque Youth